Tinjauan Sistematis Peningkatan Ketahanan Kemasan Ramah Lingkungan Berbasis Pati Singkong - Dwi Hanifah, Putri; Fraditha Lesmana, Vanny; Ayu Manika, Salwa; Mustika Nuramalia Handayani (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Conventional plastic packaging causes serious problems because it is difficult to biodegrade. Alternatives such as biodegradable cassava starch-based packaging have emerged as a potential solution due to their environmental friendliness, biodegradability and abundant availability. Although promising, cassava starch-based packaging still has many shortcomings, such as resistance to moisture and temperature. This article reviews biodegradable packaging based on cassava starch using a systematic literature review (SLR) approach and the PRISMA method. The search revealed the addition of materials such as chitosan, cellulose, essential oils, plant extracts and synthetic materials such as PVA and glycerol that can improve water resistance, heat resistance, biodegradability and tensile strength. Further research is therefore needed to optimise manioc starch so that it can be used more widely as a substitute for conventional plastics.